Regional environmental differences significantly affect the genetic structure and genetic differentiation of Carpinus tientaiensis Cheng, an endemic and extremely endangered species from China - Zhao, Runan; He, Qianqian; Chu, Xiaojie; He, Anguo; Zhang, Yuanlan; Zhu, Zunling (Frontiers in Plant Science, 2024)
Differences in topography and environment greatly affect the genetic structure and genetic differentiation of species, and endemic or endangered species with limited geographic ranges seem to be more sensitive to changes in climate and other environmental factors. The complex topography of eastern China is likely to affect genetic differentiation of plants there. Carpinus tientaiensis Cheng is a native and endangered plants from China, and exploring its genetic diversity has profound significance for protection and the collection of germplasm resources. Based on AFLP markers, this study found that C. tientaiensis has low genetic diversity, which mainly came from within populations, while Shangshantou and Tiantai Mountain populations have relatively high genetic diversity. The Nei genetic distance was closely related to geographical distance, and temperature and precipitation notablely affected the genetic variation and genetic differentiation of C. tientaiensis. Based on cpDNA, this study indicated that C. tientaiensis exhibits a moderate level of genetic diversity, and which mainly came from among populations, while Tiantai Mountain population have the highest genetic diversity. It demonstrated that there was genetic differentiation between populations, which can be divided into two independent geographical groups, but there was no significant phylogeographic structure between them. The MaxEnt model showed that climate change significantly affects its distribution, and the suitable distribution areas in Zhejiang were primarily divided into two regions, eastern Zhejiang and southern Zhejiang, and there was niche differentiation in its suitable distribution areas. Therefore, this study speculated that the climate and the terrain of mountains and hills in East China jointly shape the genetic structure of C. tientaiensis, which gived rise to an obvious north-south differentiation trend of these species, and the populations located in the hilly areas of eastern Zhejiang and the mountainous areas of southern Zhejiang formed two genetic branches respectively.